Images of rural activities on mosaic pavements in Late Antiquity in the Levant - Montgomerie, E (2015)
Images of rural activities become very popular in mosaic floor decoration in the Levant during the Late Antique period. I aim to explore different categories of iconography and discuss the images of people engaged in rural activities, such as pastoralism; hunting, fishing and activities connected with the vintage. I also aim to look at imagery that is often discussed in isolation without relation to other connected iconographic categories. The symbolic meaning of the representations of the zodiac found in synagogues, for example, is often discussed in detail without also looking at the rural calendars that appear in Christian contexts during the same period in the same region. I also want to explore the archaeological evidence for the activities that appear on the mosaic pavements. Studying both the archaeology and the iconography will, I hope, help us understand what the use of these particular categories of iconography in decorative schemes can tell us about the society that created them.